Physiotherapeutic intervention in autistic children with hypotonia: Approaches, benefits and therapeutic perspectives: Intervenção fisioterapêutica em crianças autistas com hipotonia: Abordagens, benefícios e perspectivas terapêuticas (International Seven Journal of Health Research, 2023)
Autism is a pervasive developmental disorder that can be identified before the age of three. The main characteristics of behavior are repetitive and stereotyped, limitations in activities and interests, impairment in the development of verbal and non-verbal language and quantitative deficits in interaction and communication. The objective of this work is to describe a physiotherapeutic intervention in autistic children with hypotonia: approaches, benefits and therapeutic perspectives. It is characterized by a Systematic Literature Review. Physiotherapy intervention has been shown to provide substantial benefits for autistic children with hypotonia. This includes improvements in muscle strength, motor coordination, balance and posture. Furthermore, physiotherapy can contribute to improving respiratory function and mobility, facilitating children's participation in daily activities.